Revisiting the Master-Signifier, or, Mandela and Repression - Hook, Derek; Vanheule, Stijn (Frontiers in Psychology, 2016)
The concept of the master-signifier has been subject to a variety of applications in Lacanian forms of political discourse theory and ideology critique. While there is much to be commended in literature of this sort, it often neglects salient issues pertaining to the role of master signifiers in the clinical domain of (individual) psychical economy. The popularity of the concept of the master (or ‘empty’) signifier in political discourse analysis has thus proved a double-edged sword. On the one hand it demonstrates how crucial psychical processes are performed via the operations of the signifier, extending thus the Lacanian thesis that identification is as much the outcome of linguistic and symbolic as opposed to merely psychological processes. On the other, the use of the master signifier concept within the political realm to track discursive formations tends to distance the term from the dynamics of the unconscious and operation of repression. Accordingly, this paper revisits the master signifier concept, and does so within the socio-political domain, yet while paying particular attention to the functioning of unconscious processes of fantasy and repression. More specifically, it investigates how Nelson Mandela operates as a master signifier in contemporary South Africa, as a vital means of knitting together diverse elements of post-apartheid society, enabling the fantasy of the post-apartheid nation, and holding at bay a whole series of repressed and negated undercurrents.